IMPLEMENTATION OF THE PENTAHELIX MODEL AS A BASIS FOR THE DEVELOPMENT OF FRIED ONION MSMES (MICRO, SMALL AND MEDIUM ENTERPRISES) IN PALU - Sultan, Hardianti; Nurdin, Fahruddin; Chansa Arfah, Siti Yuliaty (AGROLAND The Agricultural Sciences Journal (e-Journal), 2024)
After experiencing natural disasters and the COVID-19 pandemic, several MSMEs (Micro, Small, and Medium Enterprises) in Palu, particularly fried shallot MSMEs, have experienced a decline in production. Various measures have been taken to redevelop the fried shallot business, including the implementation of the Penta Helix collaboration. This study aims to observe the involvement and interrelation of stakeholders within the Penta Helix model in the development of MSMEs in Palu. All involved parties include the government, academics, media, the community, and the business actors themselves.The results of the study indicate that all parties have specific activities in fulfilling their respective roles. The government undertakes activities such as mentoring, issuing Business Identification Numbers (NIB), organizing exhibitions/expos/farmers' markets, conducting training, and providing e-catalog applications. Academics assist in the application of appropriate technology and enhance MSME actors' knowledge related to digital marketing. The media helps market MSME products through social media platforms like Instagram. The farming community plays a role in preparing the raw materials for fried shallots, from planting to harvesting. The fried shallot business actors, as the core participants of the Penta Helix, collaborate, synergize, and support each other in the development of fried shallot MSMEs in Palu.